2016
DOI: 10.1016/j.brainres.2016.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Focal release of neurotrophic factors by biodegradable microspheres enhance motor and sensory axonal regeneration in vitro and in vivo

Abstract: Neurotrophic factors (NTFs) promote nerve regeneration and neuronal survival after peripheral nerve injury. However, drawbacks related with administration and bioactivity during long periods limit their therapeutic application. In this study, PLGA microspheres (MPs) were used to locally release different NTFs and evaluate whether they accelerate axonal regeneration in comparison with free NTFs or controls. ELISA, SEM, UV/visible light microscopy, organotypic cultures of DRG explants and spinal cord slices were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 72 publications
1
43
0
Order By: Relevance
“…Organotypic cultures were prepared as previously described [14]. Briefly, collagen I (rat tail, #354236, Corning) diluted in basal Eagle's medium (Gibco) and sodium bicarbonate at 0.3 mg/mL was prepared as control condition.…”
Section: Methodsmentioning
confidence: 99%
“…Organotypic cultures were prepared as previously described [14]. Briefly, collagen I (rat tail, #354236, Corning) diluted in basal Eagle's medium (Gibco) and sodium bicarbonate at 0.3 mg/mL was prepared as control condition.…”
Section: Methodsmentioning
confidence: 99%
“…It is well acknowledged that BDNF plays a role as a survival factor for damaged neurons (38). This survival increasing effect of exogen BDNF is temporary and dependent on functional trkB receptors (39,40).…”
Section: Basic Effects Of Neurotrophinsmentioning
confidence: 99%
“…It has been shown that, following nerve injury, BDNF does not increase functional recovery in tests such as sciatic function index, however, it has triggering effects. Although exogenous BDNF has inefficacies in postinjury functional recovering, endogenous BDNF is known to play an important role in peripheral nerve regeneration (38,55). Anti BDNF antibody application after damage has been reported both to diminish axonal elongation and to decrease the axonal density and number (56).…”
Section: Neurotrophinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherent molecules on the surface of SCs can secrete extracellular matrix and guide the growth of axons. Neurotrophic factors secreted by SCs might be the most important factors in the microenvironment for regenerating axons (Santos et al, 2016). Growth factors enhance axonal regrowth and promote neuron survival.…”
Section: Introductionmentioning
confidence: 99%